Investigating the relationship between brand experience, brand recall and brand loyalty in experiential marketing (case study: Maral Leather) - Mehdi Ajalli; Mohammad Mahdi Mozaffari; Sahar Johari (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: In recent decades, research on the customer brand has taken a special place in various fields, including academic and business markets. Many researchers and executives of the company have concluded that one of the reasons for the brand's importance and value is its brand name for the customer, which creates value for customers and the company. As a result, marketers can use a unique value, and a higher brand name has a competitive advantage. This study investigated the relationship between brand experience, brand reputation, and brand loyalty in empirical marketing at Maral Leather Company.Methodology: The method of this research was applied in terms of purpose and descriptive-survey nature. The study's statistical population consisted of all Maral customers. Regarding the uncertainty of the population, 384 were selected as the statistical sample based on the Cochran formula. The data-gathering tool in this study was a questionnaire with 7 components and 24 items. Data analysis was performed using a structural equation test and Amos software.Findings: The research results showed that sensory experiences of events from the viewpoint of Maral customers have a positive role in creating a brand experience. The emotional experience of events Maral customers positively affects creating a brand experience. Creative experiences of events from the perspective of Maral shoppers have a positive role in creating a brand experience. Physical experiences of events from the customers' perspective have a positive effect on brand experience. The event's social identity experiences from the shoppers' standpoint have a positive role in creating a brand experience. Brand experience from customers' point of view positively and significantly affects brand refinement. Reading the customers' point of view positively and significantly affects brand loyalty.Originality/Value: Having new strategies, paying attention to the critical points in establishing, maintaining, and expanding relations with the customer, and trying to satisfy him expands the realization of customer-oriented goals and brings a base of loyal customers in the long term.